Managed aquifer recharge in Africa: taking stock and looking forward - Ebrahim, Girma Yimer; Lautze, Jonathan F.; Villholth, Karen G. (MDPI, 2020)
Climatic variability and change result in unreliable and uncertain water availability and contribute to water insecurity in Africa, particularly in arid and semi-arid areas and where water storage infrastructure is limited. Managed aquifer recharge (MAR), which comprises purposeful recharge and storage of surface runoff and treated wastewater in aquifers, serves various purposes, of which a prominent one is to provide a means to mitigate adverse impact of climate variability. Despite clear scope for this technology in Africa, the prevalence and range of MAR experiences in Africa have not been extensively examined. The objective of this article is provide an overview of MAR progress in Africa and to inform the potential for future use of this approach in the continent. Information on MAR from 52 cases in Africa listed in the Global MAR Portal and collated from relevant literature was analyzed. Cases were classified according to 13 key characteristics including objective of the MAR project, technology applied, biophysical conditions, and technical and management challenges. Results of the review indicate that: (i) the extent of MAR practice in Africa is relatively limited, (ii) the main objective of MAR in Africa is to secure and augment water supply and balance variability in supply and demand, (iii) the surface spreading/infiltration method is the most common MAR method, (iv) surface water is the main water source for MAR, and (v) the total annual recharge volume is about 158 Mm3 /year. MAR schemes exist in both urban and rural Africa, which exemplify the advancement of MAR implementation as well as its out scaling potential. Further, MAR schemes are most commonly found in areas of high inter-annual variability in water availability. If properly planned, implemented, managed, maintained and adapted to local conditions, MAR has large potential in securing water and increasing resilience in Africa. Ultimately, realizing the full potential of MAR in Africa will require undertaking hydrogeological and hydrological studies to determine feasibility of MAR, especially in geographic regions of high inter-annual climate variability and growing water demand. This, supported by increased research to gauge success of existing MAR projects and to address challenges, would help with future siting, design and implementation of MAR in Africa.